FEMINIZING ADRENOCORTICAL CARCINOMA WITH SUBCLINICAL CUSHING’S SYNDROME IN A YOUNG ADULT MALE - Hernandez, Edrome (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Adrenocortical carcinoma is a rare endocrine neoplasm which are hormonally active in almost 50% of cases. Feminizing adrenal tumors are only seen in 1-2% of ACC. CASE A 39-year-old Filipino male presented with a seven-month history of bilateral gynecomastia, intermittent epigastric pain and unintentional weight loss. Initial work-up revealed a large, heterogeneously-enhancing adrenal mass (24.9 x 12.6 x 18.2 cm) on abdominal computed tomography. Hormonal assessment showed elevated DHEAS (43.75, NV: 3-14.2 umol/L), estradiol (3212.4, NV: 11.65-82.13 pg/ml) and suppressed FSH (<0.08, NV: 1.0-10.5 mIU/ml) and LH (< 0.05, NV: 1.9-9.4 mIU/ml). Serum cortisol remains unsuppressed after 1 mg dexamethasone test (18.71 ug/dL). The clinical findings of bilateral gynecomastia with no signs of hypercortisolism associated with elevated estradiol and unsuppressed cortisol pointed to a diagnosis of adrenal tumor with mixed hormonal secretion. The patient underwent left adrenalectomy, nephrectomy, pancreatectomy with splenectomy. Histopathology revealed diffuse staining with synaptophysin and weak to moderate staining with MELAN-A and inhibin with 40% Ki-67 index consistent with adrenocortical carcinoma. Five days postoperatively, repeat hormonal workup showed a decrease in estradiol (2326.1 pg/ml) and normalization of FSH (1.48 mIU/ml). CONCLUSION Functional ACC is more likely to present with metastatic disease than non-functional ACC, and portends shorter survival. Feminizing ACC has been associated with worse prognosis that is inversely related with estradiol levels. Estrogen excess results from an increase in substrate and presence of aromatase activity within the tumor. This case underscores the importance of hormonal profiling of ACC patients and its associated prognostic implications.